The impact of covid-19 on voice, speech, and language: an interdisciplinary study of covid-19 survivors - Kuć, Joanna; Michta, Tomasz (Penerbit Universiti Kebangsaan Malaysia, 2023)
The long-term effects of a COVID-19 infection are complex and may pose significant challenges for individuals and societies. Thus, it is important to understand the full impact it may have on many aspects of a survivor’s life, including their voice, speech, and language. The study aimed to diagnose the types of speech disorders that occur in COVID-19 survivors, to investigate how long the speech disorders last, and to determine whether or not there was any correlation between the patient’s age and their score in each of the categories of the Grade, Roughness, Breathiness, Asthenia, and Strain (GRBAS) scale. A total of 30 people aged between 30 and 60 years (15 men and 15 women) participated in this study. A speech evaluation was conducted using 4 types of tests: recordings of spontaneous speech, a test of repetition of words and sentences, a monologue, and a series of automated word sequences. The perceptual evaluation of the patients’ speech was carried out by means of the GRBAS scale. We found that the majority of patients (25 out of 30) used excessive force to produce voice. We also found a significant weakening of the ability to produce voice immediately after the disease in all subjects. No significant correlations were found between the patient’s age and individual scores on the GRBAS scale. Our findings highlight the multifaceted nature of the impact of COVID-19 on communication abilities, underscoring the need for collaborative efforts across various fields to effectively address the challenges faced by COVID-19 survivors.